The Individual, the Firm, and the Family: Towards an Understanding of the Shared Frame of Reference Amongst the Family Dimension Within Family Firms - Boeckmann, Justus (2012)
Drawing on both a rigorous review of the relevant literature and data based on a multiple method collective case study analysis of three family firms, this paper explores the capacity of an emergent frame of reference within the family dimension of family businesses. Through creating three categories—vision for the family business, emotional entanglement with the family business and communication within the family dimension and ramifications thereof—the complexities underpinning this notion are elucidated. The significance of a shared frame guiding understanding and conduct as well as potential catalyst effects of communicative efforts fostering the emergence of the latter are postulated.